Living in standby-mode. Results of participatory research on the social consequences of the financial crisis in Austria - Leßmann, Ortrud; Buchner, Elisabeth (Momentum Quarterly, 2017)
This article describes the social damage of the financial and economic crisis since 2008 on older unemployed persons in Salzburg, Austria. It is part of an EU-project evaluating the social investment strategy with the help of participatory methods. The article is based on the presentation of results jointly developed with unemployed who participated in the project. The research focused on the impact of the crisis on the well-being of vulnerable groups in terms of human rights and capabilities. The framework of participatory action research, human rights and capability approach is introduced briefly. Then the social context and the resulting impact on individual well-being are presented in turns. Unemployment does not only reduce the material standard of living, but also affects health, individual, family and social life and thus the identity and self-respect of the unemployed. These are all domains protected by human rights. The Austrian labor market policy does not consistently follow the social investment idea of “investing in people” with regard to the target group of older unemployed persons.